(untitled) - Armstrong, Gary (Upper Saddle River, N.J., 2006)
How do we get you moving? By placing you--the customer--in the driver's seat. Marketing introduces the leading marketing thinking on how customer value is the driving force behind every marketing strategy. Fasten your seatbelt. Your learning journey starts here! www.prenhall.com/kotler
Keywords: Marketing,Tiếp thị